Regeneration of Commercial Tree Species and Long Term Compositional and Structural Changes in a Logged and Silviculturally Treated Brazilian Rainforest, 1955-1993 - Karfakis, T. N. S. (International Journal of Bio-resource and Stress Management, 2023)
The study presented here consisted of an extensive literature investigation on the long term silvicultural experiments of Curua Una research station in the state of Para, Brazil. The objective of the work was to assess the long term ecological and financial sustainability of a set of silvicultural treatments by using numerical figures derived from the literature related to the financial and ecological impacts of the different treatments in the scale of calendar decades. There were 5 treatments including undisturbed forest (control). The remaining four where in two categories. The first included measures to increase natural regeneration of commercial species prior to exploitation. The second included measures aimed at increasing stocking of commercials after exploitation. Adequate data was found to assess the short term success rate of all 5 treatments in terms of achieving adequate stocking of commercial tree species in sizes of trees <5 cm dbh in the first few years after initiation. It was also possible to assess tree species community composition, structure and timber financial value for trees >5 cm dbh for a period of 15 years following initial treatment for one and for 36 years after initial treatment for two others. The measures used where the stocking index (S.I.) and the establishment factor (E.F.) for the early results and the Shannon-Weinner species diversity index, total % volume of commercial tree species (TPCTV), total volume of potentially commercial tree species (TPTV), harvestable volume in the year 1993 (HV), number of stems ha-1 (STD) and stand basal area in m2 ha-1. Results showed that overall silvicultural systems that included post exploitation treatments where generally more sustainable in terms of long term biodiversity value and more financially profitable relative to systems which relied on post exploitation treatments. These results suggest that drastic revision of current legislation must take place in nations with Amazonian forest because these currently include only post exploitation silvicultural treatments.